2021
DOI: 10.1016/j.ymeth.2020.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Computational modelling of flavivirus dynamics: The ins and outs

Abstract: Enveloped viruses such as the flaviviruses represent a significant burden to human health around the world, with hundreds of millions of people each year affected by dengue alone. In an effort to improve our understanding of the molecular basis for the infective mechanisms of these viruses, extensive computational modelling approaches have been applied to elucidate their conformational dynamics. Multiscale protocols have been developed to simulate flavivirus envelopes in close accordance with biophysical data,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 130 publications
(168 reference statements)
0
8
0
Order By: Relevance
“…Although we are not there yet, progress toward this challenging goal is being made by many groups. For instance, simulations of entire viruses have already been reported, [411][412][413][414] and protocols for setting up such simulations are becoming available. 413,415,416 An advantage of using a CG model is that many conditions can be probed, in particular with placing reasonable amounts of lipids in both leaflets and an appropriate amount of interior solvent, including ions.…”
Section: Connecting To the Whole Cell Scalementioning
confidence: 99%
See 1 more Smart Citation
“…Although we are not there yet, progress toward this challenging goal is being made by many groups. For instance, simulations of entire viruses have already been reported, [411][412][413][414] and protocols for setting up such simulations are becoming available. 413,415,416 An advantage of using a CG model is that many conditions can be probed, in particular with placing reasonable amounts of lipids in both leaflets and an appropriate amount of interior solvent, including ions.…”
Section: Connecting To the Whole Cell Scalementioning
confidence: 99%
“…For instance, simulations of entire viruses have already been reported, [411][412][413][414] and protocols for setting up such simulations are becoming available. 413,415,416 An advantage of using a CG model is that many conditions can be probed, in particular with placing reasonable amounts of lipids in both leaflets and an appropriate amount of interior solvent, including ions. Initial choices often lead to instabilities which only become apparent after many microseconds of simulation.…”
Section: Connecting To the Whole Cell Scalementioning
confidence: 99%
“…In one of these studies, Pezeshkian et al studied 100 nm diameter SARS-CoV-2 envelope structures containing over 2000 proteins for 4 μs, allowing the observation of significant molecular rearrangements. The 50 nm diameter Dengue viral envelope, containing over 180 proteins, has also been probed …”
Section: Main Cg Protein Model Applicationsmentioning
confidence: 99%
“…The 50 nm diameter Dengue viral envelope, containing over 180 proteins, has also been probed. 232 IDPs have also been explored with Martini. While it was found that Martini underestimates the global dimensions of IDPs, when combined with an increase in the strength of protein−water interactions it results in conformational ensembles in good agreement with experiments 233,234 (Figure 2, c).…”
Section: Main Cg Protein Model Applicationsmentioning
confidence: 99%
“…Computational models can reveal details of the assembly process that are not accessible to experiments. However, while atomistic and near-atomistic simulations have revealed the dynamics of complete viruses [1,[37][38][39][40][41][42][43], the long timescales (ms-hours) prohibit simulating capsid assembly with atomic-resolution, ex-cept for specific steps [44,45]. Therefore, coarsegrained models have been used to study the assembly dynamics of icosahedral shells [8,.…”
Section: Introductionmentioning
confidence: 99%